Increased mortality among patients with rheumatoid arthritis and COPD: A population-based study. (July 2018) - Hyldgaard, Charlotte; Bendstrup, Elisabeth; Pedersen, Alma Becic; Ulrichsen, Sinna Pilgaard; Løkke, Anders; Hilberg, Ole; Ellingsen, Torkell
Abstract: Objectives: Only few studies have addressed the prognostic impact of chronic obstructive pulmonary disease (COPD) among patients with rheumatoid arthritis (RA), although both diseases are frequent and smoking is a shared risk factor. The objectives of the present study were to investigate the burden of COPD among RA patients and the subsequent mortality. Methods: We included patients who had a first-time diagnosis of RA in the Danish National Patient Registry between 2004 and 2016. RA patients with COPD were identified and matched with RA patients without COPD for year of birth, gender, and age at RA diagnosis. Mortality risks were assessed using Kaplan-Meier mortality curves. Adjusted hazard rate ratios (aHRRs) for death were estimated using Cox regression models. Results: The study population included 31, 333 individuals with RA. 3254 of those (10.4%) had a diagnosis of COPD and were matched to 9706 RA patients without COPD. The mortality risks in RA patients with COPD and RA patients without COPD were 4.5% and 1.5% within 2–6 months (aHRR = 3.0, CI 2.3–3.9), and 59.3% and 39.8% within 0.5–10 years (aHRR = 2.1, CI 1.9–2.1). Conclusion: Mortality was significantly increased among RA patients with COPD. The relative mortality risk remained significantly increased throughout the course of follow up.